Welfare effect of market exclusivity extension for patented medicines in Thailand: analysis of the effect of TRIPS-Plus provisions - Theerathorn Yoongthong (2017)
Under the free trade agreement negotiations with the United States and the European Union, Thailand, along with several developing countries, is required to enforce TRIPS-Plus provisions. Most developing countries claim that stringent intellectual property protection for pharmaceuticals would result in considerably higher prices for medicines, with adverse consequences for the health and well-being of their citizens. This paper empirically assesses the basis of these claims. Using a detailed product-level data set from Thailand, we estimate demand-side parameters together with key price and expenditure elasticities for a set of three main categories of antihypertensive drugs. We then use these estimates to carry out counterfactual simulations of what consumer welfare would have been, had Thailand enforced TRIPS-Plus. According to our estimation, the enforcement of TRIPS-Plus would result in a substantial accumulated consumer welfare loss to the Thai economy, ranging between 30 billion baht and 136 billion baht, within a 10-year period from 2012 to 2021. The magnitude of consumer welfare loss suggests that without clear and inclusive evidence regarding the merits of TRIPS-Plus in every aspect, Thailand should not accept any further intellectual property protection beyond the TRIPS mandates.